Expression of ATP transporters is associated with histologic regression of rectal carcinoma after neoadjuvant chemoradiotherapy - Kim, Duck-Woo; Kim, Hyun-Chul; Kim, Bo Hyung; Kim, Myung Jo; Shin, Eun (Translational Cancer Research, 2018)
Background: Preoperative chemoradiotherapy (CRT) has been established as a treatment of choice for locally advanced rectal cancer. However, the responses to CRT range very widely and there is no specific molecular marker definitively proven to be predictive of responses to CRT. We aimed to investigate the relationship between the expression of ATP-binding cassette (ABC) transporters and cancer stem cell (CSC) markers in pretreatment biopsy samples and pathological response to CRT in rectal cancer. Methods: The immunohistochemical expression of three ABC transporters (ABCG2, ABCC2, and ABCC3) and two CSC markers (SOX2 and LGR5) was determined in 76 biopsy specimens from rectal cancer patients who underwent preoperative CRT. The association between protein expression and pathologic tumor regression grade was statistically analyzed. Results: Fifty-eight (76.3%) cases were classified as chemoradio-resistant group and 18 (23.7%) cases as chemoradio-sensitive group and pathological complete remission was found in 8 (10.5%) cases. ABCG2 was frequently expressed in chemoradio-sensitive group (P=0.042), while expression of ABCC2 was found in chemoradio-resistant group (P=0.014). Low expression of ABCC2 was associated with pathologic complete remission (P=0.008). Conclusions: Immunohistochemical expression of ABCC2 and ABCG2 was associated with tumor regression after preoperative CRT in rectal cancer. In particular, ABCC2 was associated with resistance to CRT of rectal cancer. These markers might be used as biomarkers for predicting response against CRT in rectal cancer.